TLR9 Expression and Its Role in Chemosensitivity to DDP in Human Cervical Cancer Cells in vitro - 翁艳洁 王永军 石英 周文娟 王鸿雁 王常玉 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
Inflammation and infection play an important role in the pathogenesis of many cancers.Toll-like receptors（TLRs） are a class of pattern recognition receptors that recognize conserved components of microbes and trigger the immune response against invading microorganisms.Toll-like receptor 9（TLR9） recognizes non-methylated cytosine-phosphateguanosine（CpG） DNA sequences which are the surrogate for viral DNA.TLR9 may react to tumor development and progression during chronic inflammation that involves the tumor microenvironment.In order to study the role of TLR9 in cervical cancer,we analyzed the TLR9 expression in different types of HPV infection cervical cancer cells.Then we detected if CpG sequences influenced the TLR9 expression and the sensitivity to cisplatin（DDP） of these cervical cancer cells in vitro.The expression of TLR9 mRNA and protein in SiHa,Hela and C33A cells was detected by RT-PCR and Western blotting.Real-time PCR was used to examine the TLR9 expression changes induced by CpG.Chemosensitivity of the cervical cancer cells to cisplatin（DDP） was measured by MTT.It was observed that the expression of TLR9 mRNA and protein was increased gradually in SiHa（HPV16＋）,Hela（HPV18＋） and C33A（HPV-） cells.Low doses of CpG increased the TLR9 expression only in C33A（HPV-） cells,but not in SiHa（HPV16＋） and Hela（HPV18＋） cells.Furthermore,low dose of CpG significantly increased the sensitivity of C33A（HPV-） cells,but not that of SiHa（HPV16＋） and Hela（HPV18＋） cells.These results indicated that TLR9 may serve as a protective agent in HPV negative cervical cancer cells.It was concluded that TLR9 could improve the sensitivity to DDP in HPV negative cervical cancer cells and might represent a potential therapeutic option in clinical practice.